2018
DOI: 10.1108/wje-10-2017-0315
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and microstructural properties of carbon nanotubes reinforced chromium oxide coated boiler steel

Abstract: Purpose The purpose of this study was to fabricate carbon nanotubes (CNT)-reinforced chromium oxide coatings and investigate mechanical and microstructural properties of these newly developed coatings on the boiler tube steel. Design/methodology/approach 1 and 4 Wt.% CNT-reinforced Cr2O3 composite coatings were prepared and successfully deposited on ASTM-SA213-T22 (T22) boiler tube steel substrates using high-velocity oxy fuel (HVOF) thermal spraying method. Microhardness, porosity, metallography, X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The high corrosion is shown in macrograph of the uncoated substrate and weight change continuously with the very first cycle and went increasing after every cycle. Kamal et al (2017) had suggested that Na 2 SO 4 on reacts with V 2 O 5 form NaVO 3 , (Goyal et al, 2018a(Goyal et al, , 2018b(Goyal et al, , 2018c(Goyal et al, , 2019cRani et al, 2017;Zhou et al, 2017). In case of 20 per cent Cr 3 C 2 -80 per cent (NiCr) coating, the macrograph shows better surface of the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high corrosion is shown in macrograph of the uncoated substrate and weight change continuously with the very first cycle and went increasing after every cycle. Kamal et al (2017) had suggested that Na 2 SO 4 on reacts with V 2 O 5 form NaVO 3 , (Goyal et al, 2018a(Goyal et al, , 2018b(Goyal et al, , 2018c(Goyal et al, , 2019cRani et al, 2017;Zhou et al, 2017). In case of 20 per cent Cr 3 C 2 -80 per cent (NiCr) coating, the macrograph shows better surface of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…One of the protecting ways to counteract the problem of high-temperature degradation is to coat the bottom part with the protective layer using different surface coating techniques (Goyal et al, 2016). The necessary mechanical strength was provided by the composite system of a base material with a protective surface layer different in structure and chemical composition is supplied by a surface treatment can be the best choice in combining material properties (Goyal et al, 2019c(Goyal et al, , 2018b(Goyal et al, , 2018cMehta et al, 2017;Onuoha et al, 2017). Corrosion is controlled by using inhibitors, the addition of an organic inhibitor is sufficient to reduce corrosion of metals in many corrosive media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hot corrosion cycle composed of heating the test specimen for 1-h exposure in the furnace followed by 20 min of cooling to room temperature. The cyclic tests were performed to simulate an actual boiler environment (Goyal, 2018b; Goyal et al , 2017; Rani et al , 2017; Goyal and Goyal, 2020). The weight of each specimen along with the alumina boat was measured carefully on digital weighing machine after every cycle.…”
Section: Experimentation and Methodologymentioning
confidence: 99%
“…Compositions of coating powders were prepared by blending conventional zirconium yttrium, ZrO2-Y2O3 and 1 wt.% CNT, and ZrO2-Y2O3 and 4 wt.% CNT in a laboratory ball mill, using a low-energy ball milling method. Mixing of coating powders was done in a ball mill for 4 hours at 200 rpm [26]. Powder particles were asymmetric in shape and size 45 ± 10 µm.…”
Section: Coating Powdersmentioning
confidence: 99%